Effects of the use of different dentifrices with activated carbon on dental structures: integrative literature review (Research, Society and Development, 2022)
With the increasing demand for dental aesthetics especially related to color and the influence of social media, activated carbon has become one of the most used products to attract consumers. The aim of this study was to identify the consequences of the daily use of toothpastes with activated carbon for the dental structure. This is an integrative literature review carried out under the parameters of the PRISMA strategy for systematic reviews, with a search in the Pubmed and Google Academic databases. After applying the inclusion and exclusion criteria, 14 articles were selected for qualitative analysis. Dental structures seem to suffer damage with the continuous use of activated carbon as a cleaning agent, both from a structural point of view, causing enamel wear and increased surface roughness that can culminate in greater biofilm accumulation, and from a chemical point of view, interacting with fluoride ions, important in dental remineralization processes. More studies are needed to encourage stronger actions by health authorities and the Dentistry Council itself, since, although the risks of the use of products containing activated carbon for oral health seem greater than the benefits, there are still studies that show advantages in its use.